Enterprise Applications and Services in the Finance Industry 6th International Workshop, FinanceCom 2012, Barcelona, Spain, June 10, 2012. Revised Papers - Rabhi, Fethi A.; Gomber, Peter; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the proceedings of the 6th International Workshop on Enterprise Applications and Services in the Finance Industry, FinanceCom 2012, held in Barcelona, Spain, on June 10, 2012. The workshop spans multiple disciplines, including technical, service, economic, sociological, and behavioral sciences. It reflects on technologically enabled opportunities, implications, and changes due to the introduction of new business models or regulations related to the financial services industry and the financial markets. The seven papers presented were carefully reviewed and selected from numerous submissions. The topics covered are: news and text analysis; algorithmic and high-frequency trading; and the role and impact of technology.
Part I: News and Text Analysis -- Part II: Algorithmic and High Frequency Trading -- Part III: Technology Role and Impact.
Keywords: Economics; Data mining; Information systems; Management information systems; Economics/Management Science; Business Information Systems; e-Commerce/e-business.; Finance/Investment/Banking.; Computer Appl. in Administrative Data Processing; Data Mining and Knowledge Discovery; Information Systems Applications (incl. Internet).